Proximity channeling during cyanobacterial phycoerythrobilin synthesis. (26th July 2019) - Aras, Marco; Hartmann, Volker; Hartmann, Jana; Nowaczyk, Marc M.; Frankenberg‐Dinkel, Nicole
Abstract : Substrate channeling is a widespread mechanism in metabolic pathways to avoid decomposition of unstable intermediates, competing reactions, and to accelerate catalytic turnover. During the biosynthesis of light‐harvesting phycobilins in cyanobacteria, two members of the ferredoxin‐dependent bilin reductases are involved in the reduction of the open‐chain tetrapyrrole biliverdin IXα to the pink pigment phycoerythrobilin. The first reaction is catalyzed by 15, 16‐dihydrobiliverdin:ferredoxin oxidoreductase and produces the unstable intermediate 15, 16‐dihydrobiliverdin (DHBV). This intermediate is subsequently converted by phycoerythrobilin:ferredoxin oxidoreductase to the final product phycoerythrobilin. Although substrate channeling has been postulated already a decade ago, detailed experimental evidence was missing. Using a new on‐column assay employing immobilized enzyme in combination with UV‐Vis and fluorescence spectroscopy revealed that both enzymes transiently interact and that transfer of the intermediate is facilitated by a significantly higher binding affinity of DHBV toward phycoerythrobilin:ferredoxin oxidoreductase. Concluding from the presented data, the intermediate DHBV is transferred via proximity channeling. Abstract : Biosynthesis of the pink light‐harvesting and linear tetrapyrrole pigment phycoerythrobilin (PEB) in cyanobacteria requires the tandem reaction of two members of the ferredoxin‐dependent bilin reductases. PebA and PebB were shown to transfer the reaction intermediate 15, 16‐dihydrobiliverdin via proximity channeling as shown by an 'on‐column assay' and substrate binding affinities. Once produced, PEB is attached via phycobiliprotein lyases to the light‐harvesting phycobiliproteins.